Frequency of Psychogenic Non Epileptic Seizures in Patients Presenting in the Department of Neurology, Jinnah Postgraduate Medical Centre, Karachi - Muhammad, Fatima Ghulam; Sher, Khalid; Nisha, .; Ahmad, Rizwana Malahat; Farooq, Maheen; Abrar, Ateeba (Biological and Clinical Sciences Research Journal, 2025)
Psychogenic non-epileptic seizures (PNES) are clinical events that resemble epileptic seizures but lack the characteristic electrical discharges associated with epilepsy. Often underdiagnosed, PNES are frequently associated with psychological stressors and psychiatric comorbidities. In Pakistan, limited data exists on the frequency and associated factors of PNES in neurological settings. Objective: To determine the frequency of psychogenic non-epileptic seizures among patients presenting to the Department of Neurology at Jinnah Postgraduate Medical Centre (JPMC), Karachi, and to identify associated psychiatric comorbidities. Methods: This descriptive cross-sectional study was conducted at Ward 28, Department of Neurology, JPMC, Karachi, from January 13, 2025, to April 13, 2025, following ethical approval from the Institutional Review Board. A total of 151 patients aged between 12 and 60 years, of both genders, who presented with clinical features suggestive of PNES were recruited using non-probability consecutive sampling. Detailed psychiatric histories were recorded. Data were analyzed using SPSS; associations between PNES and psychiatric variables were assessed using Chi-square tests with a significance threshold of p < 0.05. Results: Out of 151 patients, PNES were confirmed in 79 individuals (51%). A significant proportion reported psychiatric comorbidities: 49.6% had post-traumatic stress, 50.3% had depression, 58.2% reported anxiety, 39% had a history of suicide attempts, and 54% were smokers. Stratified analysis revealed significant associations between PNES and anxiety (p = 0.008) as well as suicide attempts (p = 0.036), whereas depression and PTSD did not show statistically significant relationships. Conclusion: PNES were observed in over half of the study population, with strong associations identified between PNES and psychiatric conditions such as anxiety and prior suicide attempts. These findings emphasize the importance of psychiatric evaluation in patients presenting with seizure-like episodes and highlight the need for interdisciplinary management strategies.